The Impact of Enterprise Management Systems on Management Accounting in Private Companies of Iran - Hosseinzadeh, Amir; Davari, Behzad (International Journal of Economics and Financial Issues, 2018)
The research aims to explore the impact of ERP in management accounting activities. It includes a set of the developed hypotheses to evaluate how ERP training and seller support affect applying ERP systems and decision-making in five management accounting activities. The five management accounting activities include capital budgeting, budgeting, forecasting, activity-based costing and operational and reporting statements. The data collected using information questionnaire. The results show that ERP system improves quality of management accounting process, like seller support, training affects application of ERP system, but they have little impact on decision-making. Due to the research results, it can be concluded that ERP systems affect management accounting. Therefore, ability of applying ERP systems can be developed by proper training and seller support in an applied system. Keywords: Enterprise management system (ERP); Accounting management; User training; Seller support JEL Classifications: L32, M41